2010
DOI: 10.3727/096504010x12828372551867
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptors in Cancer: Therapeutic Implications

Abstract: The beta-adrenergic receptors transduce catecholamine signals to the G protein, which through a cascade of chemical reactions in cells generates highly specific parallel signals. The beta2-adrenergic receptor (ADRB2) is the most involved in the carcinogenic processes. Previous studies have determined the relationship of ADRB2 with various aspects related to cancer. Basically, it seems to be related with cell proliferation and apoptosis, chemotaxis, development of metastasis and tumor growth, and angiogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…1 As an adjunct to general endotracheal anesthesia, regional anesthesia can decrease volatile anesthestic requirements, (2, 3) decrease opioid requirements, (4, 5) block activation of the sympathetic nervous system, (6, 7) attenuate immunosuppression, (8, 9) improve tissue oxygenation, (3, 10) decrease post-operative pain (11) , and promote innate anti-tumor factors through the effects of local anesthetic. (2) …”
Section: Introductionmentioning
confidence: 99%
“…1 As an adjunct to general endotracheal anesthesia, regional anesthesia can decrease volatile anesthestic requirements, (2, 3) decrease opioid requirements, (4, 5) block activation of the sympathetic nervous system, (6, 7) attenuate immunosuppression, (8, 9) improve tissue oxygenation, (3, 10) decrease post-operative pain (11) , and promote innate anti-tumor factors through the effects of local anesthetic. (2) …”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies implicate neuroendocrine mediators, such as catecholamines and prostaglandins. Many different malignancies express receptors for catecholamines [62] and prostaglandins [63] exerting a direct tumoral effect, which includes promotion of tumor-cell proliferation [64], adhesion [65], migration [66] and invasion [64], resistance to apoptosis and anoikis [67, 68], as well as secretion of pro-angiogenic factors such as vascular endothelial growth factor [69]. Again the indirect mechanism of suppression of perioperative anti-metastatic immunity exists [44].…”
Section: Factors Influencing Loco-regional and Distant Metastatic Dismentioning
confidence: 99%
“…It has been observed that all cancers on which β-blockers have shown a suppressive effect express β-ARs (Perez-Sayans et al, 2010). β-ARs signaling pathways play a significant role in cell proliferation, differentiation and cell migration (Herlenius and Lagercrantz, 2001;Kim et al, 2008).…”
Section: Putative Role Of Catecholamines In Cancer (In Vitro and In Vmentioning
confidence: 99%